2013
DOI: 10.1111/cote.12036
|View full text |Cite
|
Sign up to set email alerts
|

A new dye‐modified poly(ethylene oxide)–poly(propylene oxide) polymer used as a dispersant for CI Disperse Red 60

Abstract: A new dye-modified poly(ethylene oxide)-poly(propylene oxide) polymer, in which the dye molecule (CI Disperse Red 60) is bonded onto polyether monoamine via a triazine ring, was synthesised for the preparation of dye aqueous dispersions and was characterised by Fourier Transform-infrared spectroscopy, 1 H nuclear magnetic resonance spectroscopy and elemental analysis. This polymer exhibits unique dispersing performance for CI Disperse Red 60. The mechanism behind the improved performance is briefly discussed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Presumably, in the case of 1-amino-4-hydroxyanthraquinone derivatives, these signals are extremely broadened peaks or shifted to the lower magnetic field side than the observation range due to interactions of intramolecular hydrogen bonds. 36 The results of 1 H NMR and HPLC showed that the chemical structures of the prototype dyestuffs were consistent with the anticipated structures; additionally, their purity was sufficiently high and required no further purification.…”
Section: The Analysis Of Dyestuffsmentioning
confidence: 52%
See 1 more Smart Citation
“…Presumably, in the case of 1-amino-4-hydroxyanthraquinone derivatives, these signals are extremely broadened peaks or shifted to the lower magnetic field side than the observation range due to interactions of intramolecular hydrogen bonds. 36 The results of 1 H NMR and HPLC showed that the chemical structures of the prototype dyestuffs were consistent with the anticipated structures; additionally, their purity was sufficiently high and required no further purification.…”
Section: The Analysis Of Dyestuffsmentioning
confidence: 52%
“…In their 1 H NMR observation range, neither amino proton nor hydroxy proton signals were observed. Presumably, in the case of 1‐amino‐4‐hydroxyanthraquinone derivatives, these signals are extremely broadened peaks or shifted to the lower magnetic field side than the observation range due to interactions of intramolecular hydrogen bonds 36 …”
Section: Resultsmentioning
confidence: 99%
“…1), in particular ethylene oxide (EO) and propylene oxide (PO), are among the most important monomers in polymer chemistry. 1,2 The aliphatic polyethers resulting from their homo-or copolymerization display extraordinarily wideranging applicability, encompassing polyols for the preparation of polyurethanes, 3,4 additives for lubrication, 5 rheology control 6 or as dispersants, 7 and also a broad employment in skin care and related daily use products (tooth paste, lip sticks). 8,9 Further examples, where a particularly rapid scientific development can be witnessed, include the use of polyethers for drug delivery, 10,11 electrochemical devices (electrolyte, membranes) [12][13][14] or the templating of nanoporous materials.…”
Section: Introductionmentioning
confidence: 99%